2019
DOI: 10.1002/er.4750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow fields and humidification of reactant and oxidant on the performance of scaled‐up PEM‐FC using CFD code

Abstract: Summary The present study focuses on three‐dimensional two‐phase CFD investigation on scaled‐up proton exchange membrane fuel cell (PEM‐FC) for an active area of 100 cm2 with different designs of serpentine and parallel flow configuration. The humidification of hydrogen and oxygen is varied from 10% to 100% to study the PEM‐FC performance. The numerical results of polarization curves predicted in this study have been numerically validated with that of the literature for both parallel and counter serpentine flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The numerical work was carried out at various cell voltages ranging from 0 V to 0.95 V under different hydrogen and oxygen humidification [36]. The dataset was considered with 10%, 50%, and 100% humidity levels with different flow channel designs likes two serpentine, three serpentine, serpentine zigzag, straight parallel, and straight zigzag [6]. The experimental study was conducted based on humidity levels.…”
Section: Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical work was carried out at various cell voltages ranging from 0 V to 0.95 V under different hydrogen and oxygen humidification [36]. The dataset was considered with 10%, 50%, and 100% humidity levels with different flow channel designs likes two serpentine, three serpentine, serpentine zigzag, straight parallel, and straight zigzag [6]. The experimental study was conducted based on humidity levels.…”
Section: Data Generationmentioning
confidence: 99%
“…Hence, this present work will contribute significantly to the existing literature by giving an in-depth analysis of scaled-up PEMFC and all other factors which affect its performance by evaluating some novel flow-field designs that numerically use CFD. A real-time numerical data analysis was implemented by [6] to enhance the performance of PEMFC with various designs.…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury and Akansu (2017) developed a novel design of convergent and divergent flow channels and showed that the performance of convergent and divergent flow channels outperformed the conventional serpentine flow channel, which was 19%-27% higher than the two conventional serpentine flow channels. Selvaraj and Rajagopal Thundil Karuppa (2019) compared the parallel, 2serpentine, 3-serpentine, serpentine zigzag, and straight zigzag flow channels and found that the power density of the straight zigzag flow was 55.4% and 11.74% higher than that of the parallel and serpentine zigzag flow channels. Liao et al (2021a) and Liao et al (2021b) analyzed zigzag parallel and conventional parallel flow channels and revealed that the zigzag flow channel could enhance mass transport along the flow direction in-between the underneath-land and underneath-channel.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PEMFC operates at lower temperatures than other types of fuel cells. Therefore, it can be used in various applications, including portable devices, automobiles, and stationary energy systems 1‐13 . So, a drastic increase in the application of PEMFC is observed in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…So, a drastic increase in the application of PEMFC is observed in the past decade. However, most of the researchers focus on materials' characterization 2,14‐22 and the effects of operation parameters on cell performance 11,12,23‐28 . Components of a PEMFC include bipolar plates (BP), gas diffusion layers (GDL), microporous layers (MPL), catalyst layers (CL), and a proton‐exchange membrane.…”
Section: Introductionmentioning
confidence: 99%